PENERAPAN PRINSIP KETERBUKAAN ATAS PUTUSAN ARBITRASE ICSID DI INDONESIA DAN PERBANDINGANNYA DENGAN BEBERAPA NEGARA - Amriani, Nurnaningsih (Jurnal Hukum dan Peradilan, 2016)
Confidentiality ICSID arbitration award already started breached by the transparency award on the opportunity provided by Article 48 paragraph (5) of the ICSID Convention and Rule 48 paragraph (4) of the ICSID Arbitration Rules. Changes in the legal norms of confidentiality to transparency of ICSID arbitration award by comparing its application in Indonesia, Malaysia, Singapore and Japan, are expected to provide great benefits for society include ICSID member countries. This dissertation research results prove that the ICSID arbitration ruling required transparency rather than confidentiality award for several important reasons and not cause problems. Even it helped realize the implementation of good governance principles. the article will note the need for unification of the laws regarding the responsibility of publication award and the need to amend the Arbitration Law in Indonesia.Keywords : principles of transparency, arbitration award, ICSID, state.